RTI: Strengthening- The Need of the Hour - Kaur, Amrik (Gyan Management Journal, 2015)
The fate of any law depends on the quality of those in charge of its implementation, the socio-political culture of the system and the vigilance and participation level of the citizens. Democracy requires an informed citizenry and transparency of information which are vital to its functioning and in order to promote transparency and accountability in the working of the Government, to curtain corruption, and to enhance people’s participation in democratic process thereby making our democracy work for the people in a real sense, Government of India has introduced Right to Information Act. This paper describes concept of RT!, ways of getting information under RT!, obligation of public authorities with some exemption available under the act Further this paper highlights impact of RT! by taking some eminent cases along with ill effect of RT! on those who bring out the society culprits through RT!. This paper also brings out obstacles in the way of RT/ and suggestions to overcome those obstacles to make RT! act more effective.